(untitled) (Research, Society and Development, 2024)
Acerola has acquired great importance due to its high vitamin C content and its potential for industrialization. However, during its processing, a quantity of waste (seed and bagasse) is generated, mainly from pulp processing. These residues can be used as new sources of food with high added value and contribute positively to the reduction of environmental impacts. Therefore, this research aimed to add value to the acerola by-product through the development of a functional yogurt. To develop this research, a complete 2² Factorial Planning and Response Surface Methodology were used. The planning included five different levels, with three central points totaling seven tests. The independent variables were: concentration of acerola by-product (%) and brown sugar (%). The responses analyzed were: water content (g/100g), acidity (g/100g), pH, ascorbic acid (mg/100g), reducing sugars (g/100g), and ash (g/100g). The Statística 7.0 software was used to analyze the results of the adopted planning. It was observed that the acerola by-product concentration factor had the greatest influence on the vast majority of responses studied.